2006
DOI: 10.1111/j.1744-7976.2006.00037.x
|View full text |Cite
|
Sign up to set email alerts
|

Tariff‐Rate Quota Liberalization: The Case of World Price Uncertainty and Supply Management

Abstract: "This paper examines the options for liberalizing tariff-rate quotas when a marketing board controls domestic production and international prices are stochastic. Lowering over-quota tariff and increasing import quota volumes are not equivalent. The trade-offs between the two types of trade reforms are examined through numerical simulations for the Canadian chicken industry. Introducing world price variability results in a distribution of welfare impacts for the different groups in the industry. Consumers and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Chicken has traditionally been treated as a single homogeneous product in trade policy analyses, regardless of production location or cut (Peterson and Orden ; Rude and Gervais ). However, Huff et al () found that the pattern of Canadian chicken consumption and trade suggests that chicken meat is two differentiated products and proposed differentiation by cut as an area for further research.…”
Section: Canadian Chicken Industry and Tradementioning
confidence: 99%
“…Chicken has traditionally been treated as a single homogeneous product in trade policy analyses, regardless of production location or cut (Peterson and Orden ; Rude and Gervais ). However, Huff et al () found that the pattern of Canadian chicken consumption and trade suggests that chicken meat is two differentiated products and proposed differentiation by cut as an area for further research.…”
Section: Canadian Chicken Industry and Tradementioning
confidence: 99%
“…6 Recent press reports suggest that one outcome of the Canada-EU negotiations will be increased preferential quota access for European cheese (Canadian Press 2012). We follow Rude and Gervais (2006) and obtain the absolute coefficient of risk aversion from the definition of the coefficient of relative risk aversion as the product of expected profit and a coefficient of relative risk aversion of 4. 7 Given higher than world prices, increased exports are not possible unless Canadian prices decline to international levels.…”
Section: Notesmentioning
confidence: 99%
“…3 Rude and Gervais (2006) and Rafajlovic and Cardwell (2010) use a partial equilibrium model and numerical simulations when analyzing trade policy in the Canadian chicken sector. The advantage of this approach is that it is not too demanding in terms of modelling and data.…”
Section: Introductionmentioning
confidence: 99%